Coulomb excitations and decays in graphene-related systems - Lin, Chiun-Yan; Wu, Jhao-Ying; Chiu, Chih-Wei; Lin, Ming-Fa (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Coulomb Excitations and Decays in Graphene-Related Systems provides an overview of the subject under the effects of lattice symmetries, layer numbers, dimensions, stacking configurations, orbital hybridizations, intralayer and interlayer hopping integrals, spin-orbital couplings, temperatures, electron/hole dopings, electric field, and magnetic quantization while presenting a new theoretical framework of the electronic properties and the electron-electron interactions together. This book presents a well-developed theoretical model and addresses important advances in essential properties and diverse excitation phenomena. Covering plenty of critical factors related to the field, the book also addresses the theoretical model which is applicable to various dimension-enriched graphene-related systems and other 2D materials, including layered graphenes, graphites, carbon nanotubes, silicene, and germanene. The text is aimed at professionals in materials science, physics, physical chemistry, and upper level students in these fields.
Theories for electronic excitations/deexcitations in layered graphenes, 3D graphites and 1D carbon nanotubes: experimental equipments -- Monolayer graphene -- AA-stacked graphenes -- AB-stacked graphenes -- ABC-stacked graphenes -- AAB-stacked graphenes -- Sliding bilayer graphene -- Diversified effects due to a perpendicular electric field -- Magnetoelectronic excitations: monolayer and bilayer graphenes -- 3D Coulomb excitations of simple hexagonal, Bernal and rhombohedral graphites -- 1D electronic excitations in metallic and semiconducting nanotubes -- Electronic excitations in monolayer silicene and germanene -- Coulomb decay rates in graphene -- Concluding remarks and perspectives.
OCLC-licensed vendor bibliographic record.
Keywords: Coulomb excitation; Electronic excitation; Radioactive decay; Graphene; SCIENCE / Chemistry / Inorganic; TECHNOLOGY / Material Science; TECHNOLOGY / Nanotechnology; SCIENCE / Physics